Weight gain in pregnancy and its correlation with birth weight of infants in ‎women Who reffered to obstetric wards of Hajar hospital in Shahrekord - masoumeh delaram; nasrin akbari (Journal of Holistic Nursing and Midwifery)
Introduction: Birth weight is one of the main determinators for somatic and mental growth in ‎infants and it is an important symptom of intrauterine growth. Thus recognition of factors that ‎affects the low birth weight and elimination of them is important.‎